Research and research capacity strengthening in the context of an emerging epidemic: Zika virus in Latin America. (23rd January 2020) - Thorson, Anna; Aslanyan, Garry; Brizuela, Vanessa; Perez, Freddy; Gómez Ponce de León, Rodolfo; Reeder, John C.; Serruya, Suzanne J.; Espinal, Marcos; Askew, Ian
Abstract : Generation of high‐quality evidence during outbreaks and health emergencies coupled with strengthening local research capacity can support a contextualized and effective epidemic response.